Anglomoc Milk / Wan Mohamad Faishal Wan Mohd Fauzi - Wan Mohd Fauzi, Wan Mohamad Faishal (2020)
Often we realized the original creamy taste of milk which enjoyed back in 1980’s has vanished. Anglomac milk combines high-quality ingredients which reminiscing the good olden days. The main goal of Full Body Anglomac Formulation is to provide a complete spectrum of nutrients to our users. Great care and attention is given to ensuring the integrity of our products.The ultimate goal of Anglomac Full-Bodied Formulation is to give a complete spectrum of nutrient to our consumers. Utmost care and attention is given to ensure the integrity of our product is protected.We proudly provide exclusive Full-Bodied Formula which gives our milk pure, rich and intense taste. Strictly NO filler ingredients are used to substitute its natural goodness and wholesomeness.